DEVELOPMENT OF INTERACTIVE SCIENCE TEACHING MATERIALS FOR ELEMENTARY SCHOOL STUDENTS - Tri Lestari; Budijanto Untung (Magister Scientiae, 2025)
This study aims to develop interactive science teaching materials for elementary school students. The development of these materials is based on a constructivist learning model that emphasizes students' active engagement in the learning process. The interactive teaching materials are designed using visual and audio media, as well as practical activities such as simple experiments and simulations, to enhance students' conceptual understanding and interest in learning science. The research method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results show that these interactive teaching materials are effective in improving students' understanding of science concepts and their learning motivation. Feedback from teachers and students indicates that the materials are easy to use, engaging, and relevant to everyday life contexts. Therefore, these teaching materials can serve as an alternative to support more meaningful and enjoyable science learning in elementary schools.